KAJIAN PENYUSUNAN MODEL PENGANGGARAN DI DAERAH BERBASIS INDEKS PEMBANGUNAN MANUSIA (IPM) (STUDY FORMULATION OF BUDGETING IN THE REGIONAL BASED ON HUMAN DEVELOPMENT INDEX) - Haryanto, Joko Tri (Pusjar SKPP Lembaga Administrasi Negara, 2015)
Along with the change of paradigm, including the Government of Local Government has an obligation to prioritize aspects of human-driven development (HDI). These priorities would have budgetary consequences. To that end, the Local Government shall allocated in the budget. The problem is, the achievement of HDI be one of the things that pose a fiscal risk in the area. This risk is usually associated with the possibility of unintended negative consequences, for example, the possibility of unexpected or slipping of HDI achievement targets. By using elasticity analysis method, this study was conducted to calculate potential fiscal risks arising in the related possibility of slipping of HDI achievement targets. Based on the analysis, it appears that the impact is different in each province (Bali, East Java, East Kalimantan and NTT NAD) in accordance with the characteristics and conditions of the area. Therefore necessary to develop a strategy that is based on the characteristics and conditions of each area in the future.Keywords: Elasticity, HDI, Budgeting Based on HDISeiring dengan perubahan paradigma, Pemerintah termasuk Pemerintah Daerah memiliki kewajiban untuk lebih memprioritaskan aspek pembangunan berbasis manusia (IPM). Prioritas tersebut tentu memiliki konsekuensi penganggar an. Unt uk i t u, Pemer i nt ah Daer ah waj i b menganggarkan dalam APBD. Permasalahannya, pencapaian target IPM menjadi salah satu hal yang menimbulkan risiko fiskal di daerah. Risiko ini biasanya dihubungkan dengan kemungkinan terjadinya akibat buruk yang tidak diinginkan, atau tidak terduga misalnya kemungkinan melesetnya target pencapaian IPM. Dengan menggunakan metode analisis elastisitas, penelitian ini dilakukan untuk menghitung potensi risiko fiskal yang muncul di daerah terkait kemungkinan melesetnya target pencapain IPM. Berdasarkan hasil analisis, terlihat bahwa dampak yang ditimbulkan berbeda-beda di masing-masing provinsi (Bali, Jatim, Kaltim, NAD dan NTT) sesuai dengan karakteristik dan kondisi daerah. Karenanya perlu disusun strategi yang mendasarkan kepada karakteristik dan kondisi daerah masing-masing ke depannya.Kata Kunci: Elastisitas, IPM, Penganggaran Berbasis IPM